Chapter III: Limits (Quarterly Journal of Economics, 1938)
Journal Article Chapter III: Limits Get access The Quarterly Journal of Economics, Volume 52, Issue Supplement, May 1938, Pages 52–92, https://doi.org/10.1093/qje/52.Supplement.52 Published: 01 May 1938